2017
DOI: 10.1001/jamapediatrics.2017.0020
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Children With Type 1 Diabetes Hospitalized for Diabetic Ketoacidosis

Abstract: IMPORTANCE Acute kidney injury (AKI) in children is associated with poor short-term and long-term health outcomes; however, the frequency of AKI in children hospitalized for diabetic ketoacidosis (DKA) has not been previously examined.OBJECTIVES To determine the proportion of children hospitalized for DKA who develop AKI and to identify the associated clinical and biochemical markers of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
192
6
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(214 citation statements)
references
References 40 publications
(67 reference statements)
13
192
6
3
Order By: Relevance
“…Nephropathy is a well‐recognized, long‐term complication of DM, and it is important to prevent or minimize other forms of potential kidney injury in this population. Pre‐renal AKI, in part due to severe dehydration from osmotic diuresis and emesis, occurs in up to 50% of adults and 64% of children with DKA . Nephrolithiasis is also a small and independent risk factor for acute and chronic renal injury, through obstructive and crystalline nephropathy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nephropathy is a well‐recognized, long‐term complication of DM, and it is important to prevent or minimize other forms of potential kidney injury in this population. Pre‐renal AKI, in part due to severe dehydration from osmotic diuresis and emesis, occurs in up to 50% of adults and 64% of children with DKA . Nephrolithiasis is also a small and independent risk factor for acute and chronic renal injury, through obstructive and crystalline nephropathy .…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI), with a rise in creatinine and uric acid, also occurs frequently in DKA and is likely due to severe dehydration . A recent study reported that 64% of children with DKA developed AKI . While studies have shown that the metabolic derangements, dehydration, and hypercalciuria that occur during DKA may predispose children to stone formation, nephrolithiasis has not been previously reported as a complication of DKA.…”
Section: Introductionmentioning
confidence: 99%
“…Other rare causes of morbidity and mortality include: Hypokalemia* Hypocalcemia, hypomagnesemia Severe hypophosphatemia* Hypochloremic alkalosis Hypoglycemia Other central nervous system complications include dural sinus thrombosis, basilar artery thrombosis, intracranial hemorrhage, cerebral infarction Venous thrombosis* Pulmonary embolism* Sepsis Rhinocerebral or pulmonary mucormycosis Aspiration pneumonia* Pulmonary edema* Adult respiratory distress syndrome (ARDS) Pneumothorax, pneumomediastinum and subcutaneous emphysema Rhabdomyolysis* Ischemic bowel necrosis Acute kidney injury including renal failure* Acute pancreatitis* …”
Section: Introduction Of Oral Fluids and Transition To Sc Insulin Injmentioning
confidence: 99%
“…In addition to the potential risk of cerebral edema from over‐estimating and over‐treating volume depletion, there are also potential risks to under‐estimating and under‐treating volume depletion in children with DKA. Recent data from our center demonstrated acute kidney injury (AKI) in 64% of children hospitalized with DKA . In that study, more severe AKI was associated with markers of volume depletion, including elevated heart rate and corrected sodium.…”
Section: Discussionmentioning
confidence: 88%
“…Height measurement is not currently included in our pre‐printed orders for DKA patients. Given the high rates of AKI in the previous study in this population, it is especially important that clear recommendations for accurate monitoring of fluid balances, urine output, and blood pressure are included in knowledge translation initiatives and addressed in pre‐printed order sets in the future so as to carefully monitor renal function in children presenting in DKA …”
Section: Discussionmentioning
confidence: 99%